Community supported agriculture - Nilsson, Mikaela; Wejåker, Kajsa (2016)
Swedish agriculture faces new challenges on an aggregated level, as well as for individual farms. The number of farms in Sweden is decreasing, but the average size of farms is increasing. Much of the structured changed can be explained by the increase in global competition and the design of the CAP within the EU. The situation also creates a detachment of the consumers from the food production. As a reaction to this large scale production, alternative food production business forms have emerged. Community supported agriculture (CSA), is a fairly new business concept in Sweden. It is an alternative food production business form that builds on close a relationship and cooperation between the producer and the consumer and the concept is well-established in other parts of the world. The economics within CSA is built on the idea of pre-payments from consumers and as a result the consumers and producers share the financial risks linked to the insecurities of not knowing the outcome of the harvest in advance. The business model has financial similarities to crowdfunding and therefore it has been useful to use information about the crowdfunding model to analyse the empirical material collected for this thesis. Trust and a strong relationship between the farmer and the consumer is vital within this business model. Therefore, theories on relationship marketing and details from the shared value concept have been used in this project. Also, in order to obtain a better understanding of the development process of new businesses, theories on business platforms have been applied to the empirical material. The aim of this project is to identify social, economic and political environmental enabeling factors for food producers who work with CSA as an alternative marketing strategy for food crops in Sweden. This was done in a case study where five business owners of CSA farms in Sweden were studied. An additional interview was also done with a project manager of a CSA project in Sweden. This project has a flexible design and subsequent to the literature review, a narrative analysis of the empirical material was finalised. The results indicate that the social factors explain why individuals choose to start CSA farms in Sweden. Contributions to society, the lack of sustainable food production and detachment from the consumers and the food production are strong motivations for developing CSA in Sweden. The increasing interest in locally produced and organic food is one of the enabling factors for developing CSA farms in Sweden. The results also reveal that the required level of bureaucracy is challenging for farmers who want to develop an alternative agricultural business form due to the complexity of the administration. Finally, the pre-payment financial model is a possibility for the farmer to receive payments all year around instead of just during the harvesting season and the risks are therefore reduced, even if there are indications of a greater pressure for the farmers to satisfy their consumers. For future research an interesting area would be to investigate a concept of cooperation between CSA farms and the public sector. Today there is little knowledge about CSA, and bureaucratic barriers which complicate the development of a possible cooperation. Further studies could also investigate if CSA might contribute to increased employment while developing the local food systems.